How to spiral questions to provoke student thinking - Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2005)
This video demonstrates an instructional technique in which the teacher guides students in examining an enduring understanding in the curriculum using a spiraling sequence of questions that leads to higher levels of thinking
Title from title screen
Keywords: Teaching; Teachers; Teaching and learning